Předběžné poznámky k multimodální transkripci pro neslyšící: příklad úpravy filmových titulků pro osoby, které mají převážně vizuální zkušenost se světem - Tamara Kováčová (AntropoWebzin, 2013)
This paper presents preliminary notes on the process of transfer of information, specifically with regard to movie subtitles, from the modality of the spoken word to that of the written word. The use of multimodal transcription and its specific use in targeting the transcription for an audience with a different cognitive experience of the world is described. Multimodal transcription is demonstrated with an analysis of about forty pre-recorded subtitles adapted for a deaf and hard-of-hearing audience for Scandinavian movies. This phenomenon offers a new area of interest for linguistics, anthropology and semiotics. Two of the most significant needs of multimodal transcription were analysed. The first one is adding information about various noises heard in the soundtrack and the second is transcription of monologues of the inner speech of characters or speeches of characters not visible in the shot. The paper discusses the use of coloured subtitles for character differentiation and specifics of transcribing information about music. Information about timing and linguistic registers used in subtitles is included, as is information about the use of reduced subtitles for movies targeting a deaf audience and the role of such transcription for educational purposes.